PsycEXTRA Dataset 2007
DOI: 10.1037/e509522010-001
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking and Intelligence Analysis

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Some of the programmes overestimated the statistical dimension of intelligence analysis at the expense of the investigative one, while others placed undue constraints upon the work of intelligence analysts by granting managers a control function over the analytical process. On a similar note, it has been observed that most currently available training programmes fail to adequately teach critical thinking skills: while training material on critical thinking is often included within courses, the reasoning process behind critical thinking tends to be addressed only minimally [14].…”
Section: Disseminationmentioning
confidence: 99%
“…Some of the programmes overestimated the statistical dimension of intelligence analysis at the expense of the investigative one, while others placed undue constraints upon the work of intelligence analysts by granting managers a control function over the analytical process. On a similar note, it has been observed that most currently available training programmes fail to adequately teach critical thinking skills: while training material on critical thinking is often included within courses, the reasoning process behind critical thinking tends to be addressed only minimally [14].…”
Section: Disseminationmentioning
confidence: 99%
“…There is a general consensus in the literature that individuals are reluctant to engage in critical thinking (Moore, 2007). This is based on widespread observation of incoherent reasoning, nonsensical beliefs, lack of respect for evidence, poor reasoning test scores, and unsupported decision-making in various populations.…”
Section: Processingmentioning
confidence: 99%
“…the cognitive capabilities, specifically the critical thinking skills, of the human analyst. For this reason, it is important to understand the inherent capabilities and limitations of the analyst and, in particular, the cognitive challenges of intelligence analysis that must be overcome through training in and application of critical thinking (Harris, 2006a(Harris, , 2006bHeuer, 1999;Moore, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, these techniques helped them in critical thinking, which is a persistent level of thinking that helps students solve problems and reviews the things already done or decisions previously taken (Stratton, 1999). Moore (2007) also adds that by using this ability the thinker improves his own judgment by taking charge of structures and thus bringing certain positive changes in their intellectual principles. We observed that by using their own critical thinking quotient, students could make the use of speaking strategies like Follow-up questions/comments, Turn-taking, Back-channel Cues, Requesting and Giving Clarification and Changing the Subject (Washburn & Christianson, 1995).…”
Section: Teachers' Instruction Interaction and Rolementioning
confidence: 99%